Nucleotide-binding domain 1 modelling: A novel molecular docking approach for screening of P-glycoprotein inhibitory activity of bioflavonoids - Pathomwat Wongrattanakamon (2018)
© 2016 Elsevier B.V. Modulation of P-glycoprotein (P-gp)’s function may lead to significant changes in the prescription drugs’ pharmacokinetic profiles and increase potential risks in occurring of drug-drug including herb-drug interactions. This computational structured-based study aimed to screen bioflavonoids which play a role in herb-drug interactions as a P-gp inhibitor utilising molecular docking analysis. 25 flavonoids were used as ligands for docking study. The mouse P-gp (code: 4Q9H) was acquired from the Protein Data Bank (PDB). Docking analysis was operated utilising AutoDock 4.2.6. A lowest estimated free energy of binding value in a cluster of each flavonoid against nucleotide-binding domain 1 (NBD1) of P-gp was analysed. The result points out the high correlation between the estimated free energies of binding and percentage of inhibitory efficiency values of flavonoids applied in the molecular modelling that is powerful and capable to predict potential P-gp interactions among flavonoids and its substrates.